Prospects for using non-fried buckwheat groats in first dishes technology - Yushchenko (Gonchar), Natalia; Bandura (Kuzmyk), Uliana; Kochubei-Lytvynenko, Oksana; Yatsenko, Olga; Belemets, Tatiana (My University, 2020)
Актуальною є розробка технології крем-супів, що дозволяє розширити можливості поєднання овочевих компонентів і надати стравам оригінальних смако-ароматичних характеристик. Основною якісною характеристикою супів-пюре є однорідна консистенція. Тому для обґрунтування технологічних параметрів приготування несмаженої гречаної крупи досліджено вплив тривалості варіння та попереднього замочування на структурно-механічні властивості суміші. Визначено раціональні технологічні параметри приготування несмаженої гречаної крупи: співвідношення крупа – вода – 1:7, температура приготування (90 ± 2) °С, тривалість процесу 15 хв з попередньою гідратацією протягом 4 год. Доведено ефективність використання несмаженої гречаної крупи у складі страв у кількості 8,0 % та розроблено композиції прянощів для перших страв: перець запашний, кмин, розмарин у співвідношенні 1:0,6:0,4.

It is urgent to develop a technology of cream-soups, allowing to widen possibilities of combining vegetable components and to give dishes with original taste-aromatic characteristics. The main quality characteristic of soups-purees is a homogenous consistence. That is why for substantiating technological parameters of non-fried buckwheat groats preparation, an influence of boiling and preliminary soaking duration on structural-mechanical properties of the mixture has been studied. Rational technological parameters of non-fried buckwheat groats preparation have been determined: groats and water ratio – 1:7, preparation temperature (90 ± 2) °С, process duration 15min with preliminary hydration for 4 hours. The effectiveness of using non-fried buckwheat groats in the composition of dishes in amount 8.0 % has been proved, and spices compositions for first dishes have been developed: fragrant pepper, cumin, rosemary in ratio 1: 0.6: 0.4
Keywords: крупа гречана; крем-суп; перші страви; крупа; реологічні властивості; водоутримуюча здатність; buckwheat groats; cream-soup; first dishes; cereal; rheological properties; water-retaining capacity; кафедра технології ресторанної і аюрведичної продукції; кафедра технології молока і молочних продуктів; кафедра біотехнології і мікробіології